ULTRASOUND AND DOPLEROMETRIC CHARACTERISTICS OF PELVIC ORGANS IN WOMEN WITH INFERTILITY AND THE HISTORY OF PRENATAL STRESS - Semenenko, I.V. (World of Medicine and Biology, 2021)
At the stage of selective examination of infertile women with prenatal stress, an ultrasound examination with Doppler examination of blood vessels was performed. The aim of the study was to increase the effectiveness of ultrasound diagnosis of genital changes of infertile women with prenatal stress, depending on the type of infertility treatment. Ultrasound is considered to be a highly informative non-invasive method, helps to establish the presence, location, structure, size of myomas, ovarian cysts, to identify concomitant pathology of the pelvic organs. Prospects for further development: the identified features of the pelvic organs will increase the frequency of natural fertile cycles and the efficiency of fertilization in in in vitro fertylization programs.